Assessing the spatiotemporal characteristics of dry deposition flux in forests and wetlands - Cong, Ling (Environmental technology, 2020)
Forests and wetlands, as two important ecosystems, play a crucial role in reducing the concentration of particulate matters. The main purpose of this study is to reveal the contribution of forest and wetland ecosystems to the reduction of particulate matter. We collected the concentration and meteorological data during the daytime in a forest and a wetland in the Olympic Park in Beijing. The main results are as follows: daily variation in the PM10 and PM2.5 concentration had the similar trend with the lowest value at midday and relatively high values in the morning and at nightfall. In the forest ecosystem, the trend of PM10 concentration at three heights followed the order: 6 m > 10 m > 1.5 m, while that of the PM2.5 followed the order 1.5 m > 10 m > 6 m. In the wetland, PM10 and PM2.5 concentrations at the three heights exhibited the same trend: 10 m > 1.5 m > 6 m. It is a comprehensive impact on concentration which may include vegetation collection rate, meteorological conditions and some kind of human activities. The PM deposition velocity of wetland was higher than that of forest, and showed the highest values in winter both in PM2.5 and PM10. The PM deposition flux in wetland was lower than forest only in autumn, and the value of deposition flux was higher than forest in other seasons. PM concentrations was positively correlated with relative humidity but negatively correlated with temperature and wind velocity